Identifikasi Telur Cacing Soil Transmitted Helminth pada Sampel Feses Petani Sayur - Vesbiana, Anggelia; Putri, Novita Eka; Solikah, Monika Putri (FORIKES, 2025)
Helminthiasis is a neglected tropical disease, also known as a Neglected Tropical Disease (NTD). According to WHO data from 2022, 1.5 billion people worldwide (24%) are infected with soil-borne helminths. The purpose of this study was to identify helminth eggs in fecal samples from vegetable farmers in Cepogo, Boyolali. Most of the local residents were farmers, and because their daily activities were closely related to the soil, farmers were at high risk of helminth egg infection. This descriptive study involved 21 vegetable farmers selected using purposive sampling. Data were collected through interviews and laboratory tests to identify helminth eggs, using the folation method to separate the helminth eggs from the feces. Interview results showed that most farmers (38.1%) had worked for 21-30 years. 19.0% used complete personal protective equipment (shoes and gloves), 90.5% of farmers had good personal hygiene, and all farmers used mixed fertilizers. Meanwhile, no Soil-Transmitted Helminth (STH) eggs were found in all farmers. It was further concluded that vegetable farmers in Cepogo, Boyolali, have good personal hygiene and self-protection practices and are free of worm eggs.Keywords: worm infestation; soil-transmitted helminth; vegetable farmers ABSTRAK Penyakit kecacingan adalah penyakit tropis yang terabaikan atau biasa disebut penyakit NTD (Neglected Tropical Disease). Menurut data WHO tahun 2022, sebanyak 1,5 miliar populasi dunia (24%) mengalami infeksi cacing yang menyebar melalui tanah. Tujuan penelitian ini adalah untuk mengidentifikasi telur cacing pada sampel feses petani sayur di Cepogo Boyolali. Sebagian besar sumber pencarian warga setempat merupakan seorang petani, karena aktivitas sehari-harinya berkaitan erat dengan tanah, petani memiliki risiko tinggi terinfeksi telur cacing. Penelitian ini merupakan studi deskriptif yang melibatkan 21 petani sayur yang dipilih secara purposive sampling. Data dikumpulkan melalui wawancara dan dilakukan pemeriksaan laboratorium untuk identifikasi telur cacing, dengan metode folasi untuk memisahkan telur cacing dari kotoran. Hasil wawancara menunjukkan bahwa sebagaian besar petani bekerja selama 21-30 tahun sebanyak 38,1%. Sebanyak 19,0% menggunakan alat pelindung diri lengkap (sepatu dan sarung tangan), 90,5% petani memiliki personal hygiene dalam kategori baik, dan seluruh petani menggunakan pupuk campuran. Sementara itu, pada seluruh petani tidak ditemukan telur cacing Soil Transmitted Helminth (STH). Selanjutnya disimpulkan bahwa petani sayur di Cepogo Boyolali memiliki personal hygiene dan perlindungan diri yang baik dan bebas dari telur cacing.Kata Kunci: kecacingan; soil transmitted helminth; petani sayur